2022
DOI: 10.1038/s41598-022-17388-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between a dietary pattern high in saturated fatty acids, dietary energy density, and sodium with coronary heart disease

Abstract: This study aimed to determine the association between dietary pattern (DP) and coronary heart disease (CHD) among high-risk adults as determined by metabolic syndrome (MetS) criteria in Malaysia. This cross-sectional study involved 365 participants with (CHD = 178; non-CHD = 187) who were recruited from selected health clinics. Dietary intake was measured using a 189-item semi-quantitative foods frequency questionnaire (FFQ) whilst anthropometry and clinical data were measured by trained researcher and biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Despite such evidence, however, some regulatory agencies believe that dietary saturated fats should be reduced and that substitution with PUFAs in lieu of SF could lead to reduced morbidity and mortality due to coronary artery disease. A vast amount of research points to this conclusion [ [47] , [48] , [49] ]. However, the data regarding the health effects of coconut oil are inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Despite such evidence, however, some regulatory agencies believe that dietary saturated fats should be reduced and that substitution with PUFAs in lieu of SF could lead to reduced morbidity and mortality due to coronary artery disease. A vast amount of research points to this conclusion [ [47] , [48] , [49] ]. However, the data regarding the health effects of coconut oil are inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Better lipid profiles were demonstrated with the virgin form of coconut oil [ 34 ]. Because coconuts are not consumed as the only food source nor are a source of saturated fat, there is a need to assess overall dietary patterns when examining diet and CVD relationships [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, cohort studies are inherently biased by design due to the reliance on self-reported data [ 3 , 29 ]. Even though the FFQs used were previously validated and then cross-verified with food records or 24 h recalls, they still ultimately rely on self-reporting and therefore can contribute to bias [ 3 , 31 , 32 , 33 , 35 ]. In addition, the FFQ used in the EPIC-Norfolk cohort was not validated for measuring saturated fat, and the Danish cohort had limited information on TFA or C17 intake [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…of 2000 mg of sodium or 5 g of salt per day. Other studies in adult Malaysians shown that 52% exceeded the dietary sodium intake recommendation from WHO while sauces are a major contributor of sodium intake (47,48). In addition, the average daily intake of saturated fat intake exceeded the recommended intake of 10% of the total daily energy intake in which breakfast contribution exceeded 20% of the daily recommended intake.…”
Section: Pro Le Of Breakfast Intakementioning
confidence: 96%